2013
DOI: 10.5194/acp-13-1469-2013
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of structural uncertainty in climate data records from GPS radio occultation

Abstract: Global Positioning System (GPS) radio occultation (RO) has provided continuous observations of the Earth's atmosphere since 2001 with global coverage, all-weather capability, and high accuracy and vertical resolution in the upper troposphere and lower stratosphere (UTLS). Precise time measurements enable long-term stability but careful processing is needed. Here we provide climate-oriented atmospheric scientists with multicenter-based results on the long-term stability of RO climatological fields for trend stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 48 publications
5
125
0
1
Order By: Relevance
“…Foelsche et al (2009) showed that the monthly means of CHAMP, GRACE-A and COSMIC global-average climatology agreed well, with a < 0.05 % discrepancy in refractivity and < 0.05 % in dry temperature for almost all months in the UTLS (Foelsche et al, 2011). Ho et al (2012) and Steiner et al (2013) demonstrate the very low structural uncertainty of the data.…”
Section: Introductionmentioning
confidence: 78%
“…Foelsche et al (2009) showed that the monthly means of CHAMP, GRACE-A and COSMIC global-average climatology agreed well, with a < 0.05 % discrepancy in refractivity and < 0.05 % in dry temperature for almost all months in the UTLS (Foelsche et al, 2011). Ho et al (2012) and Steiner et al (2013) demonstrate the very low structural uncertainty of the data.…”
Section: Introductionmentioning
confidence: 78%
“…The target domain for the comparative statistical analysis is from 5 km to 35 km height (upper 15 troposphere and lower stratosphere, UTLS), since commonly the data quality above 35 km and below 5 km is less good, due to the ionospheric effects and tropospheric multipath effects, respectively (e.g., Scherllin-Pirscher et al, 2011aSteiner et al, 2013). We first inspect difference statistics to ECMWF and subsequently to radiosondes.…”
Section: Gnos Bds Ro Single-difference and Zero-difference Results Anmentioning
confidence: 99%
“…The Earth's radio occultation (RO) technique (Melbourne et al, 1994;Ware et al, 1996) using signals from the global navigation satellite system (GNSS) has been widely used to observe 25 the atmospheric parameters (e.g., bending angle, refractivity, temperature, pressure, and water vapor) for applications such as numerical weather prediction (NWP) (e.g., Healy and Eyre, 2000;Kuo et al, 2000;Healy and Thepaut, 2006;Aparicio and Deblonde, 2008;Cucurull and Derber, 2008;Poli et al, 2008;Huang et al, 2010;Le Marshall et al, 2010;Harnisch et al, 2013) and global climate monitoring (GCM) (e.g., Steiner et al, 2001Steiner et al, , 2009Steiner et al, , 2011Steiner et al, , 201330 Atmos. Meas.…”
Section: Introductionmentioning
confidence: 99%
“…F3/C RO profiles can also be retrieved above 40 km altitude, but the data could obviously be contaminated by ionospheric residuals above that altitude (e.g., Rocken et al 1997;Syndergaard 2000). Ho et al (2012) and Steiner et al (2013) compared RO data from six different processing centers for the same time period (i.e., same ionospheric conditions) and found the largest differences at high altitudes due to different bending angle initialization approaches. Here we mainly examine the temperature and pressure observations between the 8 -20 km altitude range and the water vapor pressure below 8 km.…”
Section: Datamentioning
confidence: 99%